ONLINE COMMUNICABLE DISEASE MONITORING SYSTEM - Wong, Kok Siong (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Disease monitoring system is a system by which the spread of disease is monitored in order to establish patterns of progression. From the collection of data through this system, people in the department of health are able to analyse, interpret, and make decision to perform some actions in order to minimize the harm caused by outbreak of diseases. In Malaysia, eNotifikasi that falls under the Communicable Disease Control Information System (CDCIS) is a system used to collect data and monitor the diseases from spreading. Unfortunately, the health officer from Pejahat Kesihatan Bahagian, Kota Sümarahan, had claimed that the current system only collects data from the authorised medical personnel, but not helping them to know the current situation of the disease spread. Thus, the project is conducted to design and develop an online communicable disease monitoring system (OCDMS) in order to prevent the potential diseases from spreading rapidly. Data presentations using various type of data visualization were developed for a better view and decision making. Forecasting actions can be planned based on the prediction of disease spread via a mathematical model which is incorporated into the system. Reviews on some of the similar systems were done to collect more information in providing a better solution to the current problem.